Urban-Rural Gaps in Breastfeeding Practices: Evidence From Lao People's Democratic Republic - Jordyn T. Wallenborn; Jordyn T. Wallenborn; Camille B. Valera; Sengchanh Kounnavong; Somphou Sayasone; Peter Odermatt; Peter Odermatt; Günther Fink; Günther Fink (Frontiers Media S.A., 2021)
Objectives: Breastfeeding rates are decreasing rapidly in many low and middle-income countries, disproportionately affecting urban residences. We use data from Lao People's Democratic Republic to identify primary mechanisms underlying the urban-rural gap in breastfeeding practices.Methods: We used data from the 2017 Lao Social Indicator Survey II. Residence was categorized as large-urban (>1 million), small-urban (<1 Million), and rural. Multivariable logistic regression provided odds ratios and 95% confidence intervals (CI) to identify factors attributing to the urban-rural differences in complying with World Health Organization's breastfeeding recommendations for children <24 months.Results: Mothers in large-urban residences had 3.78 (95% confidence intervals: 1.19, 11.95) and 4.67 (95% CI: 2.30, 9.46) higher odds of non-compliance with exclusive and complementary breastfeeding recommendations, respectively, than mothers living in rural areas in bivariate models. Breastfeeding differentials between small urban and rural residences were largely explained by differences in maternal education and household wealth.Conclusion: Results of our paper suggest large disparities in breastfeeding practices between large-urban, small-urban, and rural residences.